Patricio Fontana, Arlt va al cine. Buenos Aires, Libraria, 2010, 145 páginas - Juárez, Laura (2010)
Fil: Juárez, Laura. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación; Argentina.